MENUMBUHKAN KARAKTER MANDIRI PESERTA DIDIK DI MASA PEMBELAJARAN ONLINE SEBAGAI IMPLIKASI DARI COVID-19 DI SMK NEGERI 5 DENPASAR - I Kadek Arta Jaya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Currently, almost all countries around the world are experiencing a crisis due to being infected with the Corona Virus Disease (COVID-19). This virus originally appeared in China, to be precise in the City of Wuhan in December at the end of 2019. Covid-19 is very dangerous because the transmission from human to other humans is so fast and even until now there is no medicine that can cope with the corona virus, including in Indonesia, which is increasingly increasing the number of COVID-19 cases. As a result of this epidemic, it has had a huge impact on almost all aspects of life, starting from the economic, social, cultural and even educational aspects. Almost all levels of education that were initially carried out in school learning have now shifted to online learning. This journal aims to explain the effect of independent character education on students during online / online learning. This study is carried out through literature study by looking at the results of surveys and journals from electronic media. The conclusion of this journal is that there is an implementation of self- cultivation in students during the online learning process at SMK Negeri 5 Denpasar.